Cardiac and respiratory activities induce temporal changes in cerebral blood volume, balanced by a mirror CSF volume displacement in the spinal canal - Pan Liu; Kimi Owashi; Heimiri Monnier; Serge Metanbou; Cyrille Capel; Olivier Balédent (NeuroImage)
Understanding cerebrospinal fluid (CSF) dynamics is crucial for elucidating the pathogenesis and diagnosis of neurodegenerative diseases. The primary mechanisms driving CSF oscillations remain a topic of debate. This study investigates whether cerebral blood volume displacement (CBV), modulated by breathing and cardiac activity, is the predominant drivers of CSF oscillations. We examined 12 healthy volunteers (aged 20–34 years) using a clinical 3T MRI scanner to quantify cerebral blood flow at the intracranial level and CSF flow at the C2-C3 spinal level under free and deep breathing conditions, utilizing real-time phase-contrast sequences. We then obtained CBV and CSF volume displacement (CSFV) curves by integrating the flow rate signals. Cardiac and respiratory signals were recorded during acquisition to reconstruct cardiac-driven and breath-driven CBV and CSFV curves.During deep breathing, compared to free breathing, the total cerebral arterial flow rate decreased by 29 % (from 12.5 ml/s to 8.8 ml/s), and the duration of the cardiac cycle period shortened by 15 % (0.90 s to 0.77 s), leading to reductions of 37 % and 23 % in cardiac-driven CBV and CSFV amplitudes, respectively. Conversely, breath-driven CBV and CSFV amplitudes increased substantially by 207 % and 326 %, respectively. Notably, during free breathing, cardiac-driven CBV and CSFV were significantly greater than their breath-driven counterparts; however, during deep breathing, the amplitudes of cardiac-driven and breath-driven CBV and CSFV did not differ significantly. CBV and CSFV curves demonstrated strong coupled inverse oscillation under both breathing conditions, with consistent CSF inflow toward the intracranial compartment during inspiration.This study quantifies the contributions of cardiac and breathing activities to CBV and CSFV under varying breathing patterns, confirming that CBV changes, driven by cardiac and respiratory activities, are strongly inversely coupled with CSF oscillations. These findings enhance our understanding of CSF circulation mechanisms and offer potential diagnostic implications for neurodegenerative diseases.